The Principle Of Due Process In Disciplinary Sanctions For Civil Servants In Indonesia: Comparative Study Of Government Regulation Number 53 Of 2010 And Number 94 Of 2021 - Ahmad Baihaqi Midhol (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the application of the due process principle in the procedure for imposing disciplinary penalties on the civil servants based on a comparison of Government Regulation Number 53 of 2010 and Government Regulation Number 94 of 2021. The four main principles of due process namely notice, hearing, impartiality and right to appeal are the basis for evaluation. The analysis shows that both regulations include notice and hearing as a form of respect for the right to self-defense. However, in the aspect of impartiality, there is a weakness because the initial examination is carried out by direct superiors who have a potential conflict of interest. Government Regulation 94 of 2021 provides greater rights of objection or appeal than Government Regulation 53 of 2010 but still does not include an explicit conflict of interest prevention mechanism. Therefore, this study recommends revising regulations and strengthening independent supervision mechanisms to improve objectivity and integrity in civil servant’s discipline enforcement.